Pengembangan SDM dan Penilaian Kinerja pada PT Bio Nusantara Teknologi Bengkulu - Tri Wahyuni; Sazuli Sazuli; Desi Karlina; Indra Cahyadinata; Septri Widiono; Alia Azmi (Asosiasi Riset Ilmu Manajemen dan Bisnis Indonesia, 2026)
Human resources (HR) are a strategic pillar in determining the success and competitiveness of agribusiness companies in the era of globalization. This study aims to analyze the implementation of training programs, HR development, and performance appraisal systems, as well as formulate strategies to optimize HR management at PT Bio Nusantara Teknologi Bengkulu. The research method uses a descriptive quantitative approach with a simple random sampling technique for 20 respondents (10% of the total 200 employees). Data collection was carried out through structured questionnaires and direct observation, which were then analyzed using the Internal Factor Evaluation (IFAS) matrix, External Factor Evaluation (EFAS), and SWOT matrix analysis. The results show that the training program and performance appraisal have been running very well, where the assessment is carried out periodically and objectively and has a direct impact on increasing employee motivation, responsibility, and work productivity. The evaluation results show an IFAS score of 2.7 (fairly strong) and an EFAS score of 2.6 (fairly adaptive). Based on the SWOT analysis coordinates, the company is in Quadrant I (Strengths-Opportunities/SO Strategies) with a difference between internal and external factors of 0.8 each. The implication of this position is that companies must implement aggressive strategies by leveraging advances in digital technology (such as e-learning) and expanding their external collaboration networks to maintain their competitive advantage in the industry.